A New Behavioral Test and Associated Genetic Tools Highlight the Function of Ventral Abdominal Muscles in Adult Drosophila - Pons, Marine; Soulard, Claire; Soustelle, Laurent; Parmentier, Marie-Laure; Grau, Yves; Layalle, Sophie (Frontiers in Cellular Neuroscience, 2017)
The function of the nervous system in complex animals is reflected by the achievement of specific behaviors. For years in Drosophila, both simple and complex behaviors have been studied and their genetic bases have emerged. The neuromuscular junction is maybe one of the prototypal simplest examples. A motor neuron establishes synaptic connections on its muscle cell target and elicits behavior: the muscle contraction. Different muscles in adult fly are related to specific behaviors. For example, the thoracic muscles are associated with flight and the leg muscles are associated with locomotion. However, specific tools are still lacking for the study of cellular physiology in distinct motor neuron subpopulations. Here we decided to use the abdominal muscles and in particular the ventral abdominal muscles (VAMs) in adult Drosophila as new model to link a precise behavior to specific motor neurons. Hence, we developed a new behavioral test based on the folding movement of the adult abdomen. Further, we performed a genetic screen and identify two specific Gal4 lines with restricted expression patterns to the adult motor neurons innervating the VAMs or their precursor cells. Using these genetic tools, we showed that the lack of the VAMs or the loss of the synaptic transmission in their innervating motor neurons lead to a significant impairment of the abdomen folding behavior. All together, our results allow establishing a direct link between specific motor neurons and muscles for the realization of particular behavior: the folding behavior of the abdomen in Drosophila.